STUDENTS’ SELF-REGULATION OF MOTIVATION IN READING - Ranggi Mulia Bestari; Ouda Teda Ena; Paulus Kuswandono (IKIP Siliwangi, 2023)
Self-regulated learning is students’ ability in regulating their learning behavior based on their learning strategies, characteristics, and individual process. Self-regulated learning belongs to the cognitive, metacognitive, behavioral, motivational, and emotional aspects of learning. In English language learning, four skills should be mastered by the student, they are reading, listening, speaking, and writing. Reading skill means integrating the formation and reasoning of a text. This research aims to investigate the relationship between self-regulation motivations in students’ reading skills. In this research, the researcher used a mixed method to collect and analyze the data. In collecting the data, there were 33 participants in this research. The instruments used in this research were use questionnaires and interviews. The questionnaire contains 11 close-ended questions and 3 open-ended questions. The result of this study shows that students are applying five strategies in their motivation regulation, they are self-consequating, environmental structuring, goal-oriented self-talk, interest enhancement, and self-handicapping. Furthermore, some students doing procrastination. The implication provided to students, school management, and boarding management. Keywords: Self-Regulation; Motivation Regulation; Reading Skill